Identification of plant vacuolar transporters mediating phosphate storage - Tzu-Yin Liu (Nature Portfolio, 2016)
The plant vacuole acts as a storage compartment for inorganic phosphate and buffers cytoplasmic phosphate concentration. Here, Liu et al. identify a group of vacuolar phosphate transporters in Arabidopsisthat are required for plant growth in response to fluctuating availability of phosphate.